Persepsi Metode Yanbu’a dan Pengaruh Terhadap Hasil Belajar Membaca Al Qur’an di TPQ Raudlatul Mubtadi-ien Kediri - Niswatul Mutiah; A. Jauhar Fuad (Universitas Islam Tribakti Lirboyo Kediri, 2020)
A quantitative approach is used in this research using non-parametric statistical analysis of the Kendall tau formula. This form of research is based on field research conducted at TPQ Raudlatul Mubtadi-ien Kediri. The researcher used the data collection method by interviewing and distributing questionnaires with a sample of 48% of the 125 students, who were studied, namely the students of TPQ Raudlatul Mubtadi-ien Kediri who were class II and III ibtida 'who recited with the yanbu'a method. In this study, the researcher will look for the influence of the yanbu'a learning method on the reading potential of the students of TPQ Raudlatul Mubtadi-ien. This Al Qur'an reading program is available at the TPQ Raudlatul Mubtadi-ien from kindergarten to ibtida 'class III. The findings of this research are balanced students' perceptions and reading potential of the Qur'an at a high level, however, in the hypothesis test it is rejected with a value of 0.106 with a significance of 0.130, which means that most of the students do not understand and are not aware of learning with the yanbu'a method, students only focus on the Koran.